Temporal variations of reference evapotranspiration and its sensitivity to meteorological factors in Heihe River Basin, China - Jie Zhao; Zong-xue Xu; De-peng Zuo; Xu-ming Wang (Water Science and Engineering, 2015)
On the basis of daily meteorological data from 15 meteorological stations in the Heihe River Basin (HRB) during the period from 1959 to 2012, long-term trends of reference evapotranspiration (ET0) and key meteorological factors that affect ET0 were analyzed using the Mann-Kendall test. The evaporation paradox was also investigated at 15 meteorological stations. In order to explore the contribution of key meteorological factors to the temporal variation of ET0, a sensitivity coefficient method was employed in this study. The results show that: (1) mean annual air temperature significantly increased at all 15 meteorological stations, while the mean annual ET0 decreased at most of sites; (2) the evaporation paradox did exist in the HRB, while the evaporation paradox was not continuous in space and time; and (3) relative humidity was the most sensitive meteorological factor with regard to the temporal variation of ET0 in the HRB, followed by wind speed, air temperature, and solar radiation. Air temperature and solar radiation contributed most to the temporal variation of ET0 in the upper reaches; solar radiation and wind speed were the determining factors for the temporal variation of ET0 in the middle-lower reaches.